Níveis de lisina em dietas para reprodutores de Rhamdia voulezi em tanques-rede - Diemer, Odair [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim was to evaluate the levels of lysine in diets to breeding of Rhamdia voulezi in cages evaluating the productive, reproductive performance, hormonal characteristics, organosomatic indices and amino acid incorporation in oocytes and in the carcass in. Four hundred fish were used with an average initial weight of 35.18 ± 0.25g, distributed in a randomized design with four treatments and four replications in 16 cages with 25 fish each. The treatments consisted of four diets designed to contain levels of total lysine of 1.20; 1.40; 1.60 and 1.80% with 30% crude protein and 3,500 kcal kg-1 digestible energy. After fed for 185 days it was randomly selected 18 males that liberated semen under mild compression of the abdomen and 18 females who had rounded abdomen, swollen and reddish urogenital papilla, and taken to the laboratory where they were weighed, measured, submitted to hypophysation (with crude carp pituitary extract (EHC)) at a dose of 2.5 mg.kg-1 in males and 5.5 mg.kg-1 for females. After 240 thermal units accumulated, the semen was collected for fertilization and evaluation of the following parameters: semen volume, duration and rate of sperm motility, sperm survival index, sperm concentration, percentage of normal sperm, pH and osmolarity. At the same time, the oocyties was colellected and divided into portions: Gilson solution (oocyte diameter), frozen (amino acid analysis) and the remainder in fertilized with pre-analyzed semen and willing conical incubators (20L) for measurement of reproductive parameters. Then, the blood was collected (analysis of cortisol, estradiol and testosterone), after it they were sacrificed by dislocation of the cervical spine, dissected, where the ovaries, testicles, liver, fat and viscera were removed, weighed and estimated the respective organosomatic indices. Carcasses were dried for analysis of amino acids. In males was verified effect (p<0.05) for the final weight, weight gain, feed ...

Objetivou-se avaliar os níveis de lisina em dietas para reprodutores de Rhamdia voulezi em tanques-rede por meio do desempenho produtivo, reprodutivo, características hormonais, índices corpóreos e incorporação de aminoácidos. Foram utilizados 400 peixes com peso médio inicial de 35,18±0,25g, distribuídos em um delineamento casualizado com quatro tratamentos e quatro repetições, em 16 tanques-rede com 25 peixes. Os tratamentos foram constituídos por quatro rações elaboradas de modo a conter níveis de lisina total de 1,20; 1,40; 1,60 e 1,80% com 30% de proteína bruta e 3.500 kcal kg-1 de energia digestível. Depois de alimentados por 185 dias foram selecionados aleatoriamente 18 machos que liberavam sêmen sob leve compressão da região abdominal e 18 fêmeas que apresentavam abdômen arredondado, papila urogenital intumescida e avermelhada e conduzidos para o laboratório onde foram pesados, medidos, submetidos à hipofisação (extrato bruto de hipófise de carpa - EHC, na dosagem de 2,5 mg.kg-1 para os machos e 5,5 mg.kg-1 para fêmeas). Após 240 unidades térmicas acumuladas o sêmen foi coletado para avaliar os seguintes parâmetros: volume seminal, tempo de duração e taxa de motilidade espermática, índice de sobrevivência espermática, concentração espermática, porcentagem de espermatozóides normais, pH e osmolaridade. Ao mesmo tempo os ovócitos foram coletados e divididos em parcelas: solução de Gilson (diâmetro dos ovócitos), congeladas (análise de aminoácidos) e o restante fertilizado com o semen pré-analisado e dispostos em incubadoras cônicas (20L) para aferição dos parâmetros reprodutivos. Em seguida, o sangue foi coletado (análise de cortisol, estradiol e testosterona), posteriormente, sacrificados por deslocamento da coluna cervical, dissecados, onde os ovários, testículos, fígado, gordura e vísceras foram retirados, pesados e estimados os respectivos índices corpóreos. As carcaças...
Keywords: Peixe - Nutrição; Peixe - Reprodução; Tanques; Lisina na nutrição animal; Desempenho; Nutrition